Immune Antibodies and Helminth Products Drive CXCR2-Dependent Macrophage-Myofibroblast Crosstalk to Promote Intestinal Repair - Esser-von Bieren, Julia (PLoS Pathog, 2015)
Helminth parasites can cause considerable damage when migrating through host tissues, thus making rapid tissue repair imperative to prevent bleeding and bacterial dissemination particularly during enteric infection. However, how protective type 2 responses targeted against these tissue-disruptive multicellular parasites might contribute to homeostatic wound healing in the intestine has remained unclear. Here, we observed that mice lacking antibodies (Aid(-/-)) or activating Fc receptors (Fcrg(-/-)) displayed impaired intestinal repair following infection with the murine helminth Heligmosomoides polygyrus bakeri (Hpb), whilst transfer of immune serum could partially restore chemokine production and rescue wound healing in Aid(-/-) mice. Impaired healing was associated with a reduced expression of CXCR2 ligands (CXCL2/3) by macrophages (MΦ) and myofibroblasts (MF) within intestinal lesions. Whilst antibodies and helminths together triggered CXCL2 production by MΦ in vitro via surface FcR engagement, chemokine secretion by intestinal MF was elicited by helminths directly via Fcrg-chain/dectin2 signaling. Blockade of CXCR2 during Hpb challenge infection reproduced the delayed wound repair observed in helminth infected Aid(-/-) and Fcrg(-/-) mice. Finally, conditioned media from human MΦ stimulated with infective larvae of the helminth Ascaris suum together with immune serum, promoted CXCR2-dependent scratch wound closure by human MF in vitro. Collectively our findings suggest that helminths and antibodies instruct a chemokine driven MΦ-MF crosstalk to promote intestinal repair, a capacity that may be harnessed in clinical settings of impaired wound healing.